How adolescent motherhood is perceived and influenced by sociocultural factors: A sociological qualitative study of Sindh province, Pakistan - Nadia Agha; Rahim Dad Rind (PLoS ONE, 2025)
Background In Low and Middle-Income Countries (LMICs), 21 million adolescent girls aged between 15 and 19 years become pregnant each year. Adolescent girls in South Asia have the shortest interval to begin maternity, i.e., within 1–2 years of marriage. There is limited evidence on the associated factors of adolescent pregnancy and motherhood in rural areas where socioeconomic indicators about women are weak. This study examined the sociocultural factors intertwined together and gave rise to adolescent motherhood. Methods This exploratory qualitative study was conducted in rural and less privileged areas in Pakistan’s Sindh province. Data was collected from August 05 to September 17, 2023, and 37 young women, who experienced early marriage, adolescent pregnancy and motherhood, were interviewed. The data was translated and transcribed verbatim. Braun & Clark’s six-step data analysis Model was used to create codes, develop themes and generate a report. Results The findings of the study show that child and close kin group marriage, poor socioeconomic conditions and social norms encouraged adolescent motherhood among young women. One’s association with the extended family also increased the likelihood of early maternity because different family members exerted social pressure to become a mother. This made the girls anxious to begin motherhood soon after marriage. However, these young mothers were unaware of adolescent’s motherhood’s social, psychological and physical consequences. They embraced it happily because it was considered a way of strengthening their position in the family. Conclusion This study confirms the negative consequences of adolescent motherhood in terms of school dropout and poor health outcomes. Based on these findings, we suggest addressing poverty and female dropout rates to prevent child marriage and adolescent pregnancy. Health providers must be trained to provide awareness and psychological support to girls experiencing adolescent motherhood. The government must initiate sexual and reproductive health education and engage community heads and religious leaders to educate communities about the social and health consequences of child marriage, adolescent pregnancy and motherhood.